Seleksi Dan Identifikasi Bakteri Penambat Nitrogen Pada Perakaran Tanaman Kacang Hijau (Vigna radiata L) Dan Tomat (Solanum lycopersicum L) Di Kabupaten Belu: - - Anastasia Buak; Lukas Pardosi; Gergonius Fallo (Universitas Nusantara PGRI Kediri, 2022)
Nitrogen fixing bacteria are often called diazotroph bacteria which are able to use air nitrogen as a nitrogen source for their growth. Nitrogen fixing bacteria have the ability to increase the efficiency of N- available in the soil. The purpose of this study was to determine the morphological and biochemical characters of nitrogen-fixing bacteria from the roots of mung bean and tomato plants in Belu Regency. Isolation of nitrogen fixing bacteria by scratch method and spread on NA media. While the selection of nitrogen fixing bacteria using Jensen agar media. The results of the isolation obtained 12 isolates. Six isolates from roots of tomato plants and six isolates from roots of mung bean plants. The morphological characters of the 12 isolates were generally round in shape, small in size, flat in elevation and milky white in color. The selection results showed that 3 isolates grew on Jansen agar media, namely RKHB05, RKHB06, and RTB06. The result of gram staining showed that RKHB05, RKHB06 isolates were gram negative and had cocci cell form, while RTB06 isolates were gram positive with bacillus cell forms. The 3 isolates were positive for motility test, Citrate test, TSIA, and Catalase test